Grand Kampar Hotel Kampar / Amirul Ammar Huzaimi ... [et al.] - Huzaimi, Amirul Ammar; Muhamad Zaidi, Muhamad Haikal; Azami, Muhammad Aiman; Mohamed, Nur Anis Asneeda; Waruzi, Wan Nurshazwani (2016)
Final Integrated Project consist of Ten (10) chapter. The case study is Grand Kampar Hotel (GKH). In first chapter, it story about the building information include the building background, the building facilities and utilities and location of the building. In second chapter, there are many subject about organization of the building. In this chapter, there organization structure, scope and responsibility of maintenance department. In third chapter, it has GKH vision, mission and objective, maintenance quality and GKH planning of maintenance. In fourth chapter, it about building design and their technology. From sub-structure until superstructure, 14 building services and external work has been inform in this chapter. This chapter also has been inform about special technology that Grand Kampar Hotel used for maintenance. In fifth chapter, it about building condition assessment. In this chapter, it inform the 15 defect has been detect on building survey of building that already nine (9) years old. The defect retification cost also has in this chapter. In sixth chapter, it inform about maintenance strategy for the future. In seventh chapter, it about legal aspect. It has inform about the building service contract agreement and service level agreement. It also consisted of Uniform Building by Law 1984, Act 133, Street, Drainage & Building 1974, Occupational Safety & Health 1994 (Osha) and Electricity Supply Act 1990 (Act 447). In eighth chapter, it inform about the financial of maintenance. Also have forecast budget from 2015 until 2018. In this chapter also have the analysis of financial. In ninth chapter, it inform about building problem and recommendation to fix that. And last chapter, it inform about the whole conclusion.